A Local Wisdom-Based Marine Management Model To Improve Animal Protein Utilization And Children's Nutrition In East Flores District - Kaha, Hendrikus Likusina (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2026)
The study formulates a marine management model based on local wisdom to increase the use of animal protein and improve the nutritional status of children in East Flores Regency. Although this region has abundant marine resource potential, children’s animal protein consumption remains low due to sub-optimal distribution of catches and limited nutritional education. A mixed methods approach with a sequential explanatory design was used, involving 120 fishing households as a sample. Multiple linear regression analysis showed that the distribution of catch for family consumption (β = 0,421; p < 0,01), frequency of fish consumption (β = 0,365; p < 0,05), and processed seafood diversification (β = 0,287; p < 0,05) had a significant effect on children’s nutritional status. Qualitative findings emphasize the importance of integrating local wisdom, strengthening traditional institutions, and community-based nutrition education. The developed model integrates catch distribution management, nutrition education, and marine product diversification, thereby bridging the marine and health sectors. This research also provides theoretical contributions to the development of community-based coastal governance and practical contributions to local policies to improve child nutrition quality.